Question and Answers Forum

All Questions      Topic List

Relation and Functions Questions

Previous in All Question      Next in All Question      

Previous in Relation and Functions      Next in Relation and Functions      

Question Number 926 by 123456 last updated on 26/Apr/15

a(n,m)= { (m,(n≤0)),((na(n+m−1,m)+m),(n>0∨m≤0)),((na(n−m,m−1)+m+m^2 ),(n>0∨m>0)) :}  a(5,5)=???  a(10,10)=??

$${a}\left({n},{m}\right)=\begin{cases}{{m}}&{{n}\leqslant\mathrm{0}}\\{{na}\left({n}+{m}−\mathrm{1},{m}\right)+{m}}&{{n}>\mathrm{0}\vee{m}\leqslant\mathrm{0}}\\{{na}\left({n}−{m},{m}−\mathrm{1}\right)+{m}+{m}^{\mathrm{2}} }&{{n}>\mathrm{0}\vee{m}>\mathrm{0}}\end{cases} \\ $$ $${a}\left(\mathrm{5},\mathrm{5}\right)=??? \\ $$ $${a}\left(\mathrm{10},\mathrm{10}\right)=?? \\ $$

Commented by123456 last updated on 27/Apr/15

a(0,m)=m

$${a}\left(\mathrm{0},{m}\right)={m} \\ $$

Commented by123456 last updated on 27/Apr/15

a(1,m)= { ((2m),(m≤0)),((4m−2),(0<m<1)),((m^2 +2m−1),(m≥1)) :}  m≤0  a(1,m)=a(m,m)+m=m+m=2m  m>0  a(1,m)=a(1−m,m−1)+m+m^2   m≥1  a(1−m,m−1)=m−1  a(1,m)=m−1+m+m^2 =m^2 +2m−1  0<m<1  a(1−m,m−1)=(1−m)a(−1,m−1)+m−1  =(1−m)(m−1)+m−1  =−(m−1)^2 +m−1  =−(m^2 −2m+1)+m−1  =−m^2 +2m−1+m−1  =−m^2 +3m−2  a(1,m)=−m^2 +3m−2+m+m^2 =4m−2

$${a}\left(\mathrm{1},{m}\right)=\begin{cases}{\mathrm{2}{m}}&{{m}\leqslant\mathrm{0}}\\{\mathrm{4}{m}−\mathrm{2}}&{\mathrm{0}<{m}<\mathrm{1}}\\{{m}^{\mathrm{2}} +\mathrm{2}{m}−\mathrm{1}}&{{m}\geqslant\mathrm{1}}\end{cases} \\ $$ $${m}\leqslant\mathrm{0} \\ $$ $${a}\left(\mathrm{1},{m}\right)={a}\left({m},{m}\right)+{m}={m}+{m}=\mathrm{2}{m} \\ $$ $${m}>\mathrm{0} \\ $$ $${a}\left(\mathrm{1},{m}\right)={a}\left(\mathrm{1}−{m},{m}−\mathrm{1}\right)+{m}+{m}^{\mathrm{2}} \\ $$ $${m}\geqslant\mathrm{1} \\ $$ $${a}\left(\mathrm{1}−{m},{m}−\mathrm{1}\right)={m}−\mathrm{1} \\ $$ $${a}\left(\mathrm{1},{m}\right)={m}−\mathrm{1}+{m}+{m}^{\mathrm{2}} ={m}^{\mathrm{2}} +\mathrm{2}{m}−\mathrm{1} \\ $$ $$\mathrm{0}<{m}<\mathrm{1} \\ $$ $${a}\left(\mathrm{1}−{m},{m}−\mathrm{1}\right)=\left(\mathrm{1}−{m}\right){a}\left(−\mathrm{1},{m}−\mathrm{1}\right)+{m}−\mathrm{1} \\ $$ $$=\left(\mathrm{1}−{m}\right)\left({m}−\mathrm{1}\right)+{m}−\mathrm{1} \\ $$ $$=−\left({m}−\mathrm{1}\right)^{\mathrm{2}} +{m}−\mathrm{1} \\ $$ $$=−\left({m}^{\mathrm{2}} −\mathrm{2}{m}+\mathrm{1}\right)+{m}−\mathrm{1} \\ $$ $$=−{m}^{\mathrm{2}} +\mathrm{2}{m}−\mathrm{1}+{m}−\mathrm{1} \\ $$ $$=−{m}^{\mathrm{2}} +\mathrm{3}{m}−\mathrm{2} \\ $$ $${a}\left(\mathrm{1},{m}\right)=−{m}^{\mathrm{2}} +\mathrm{3}{m}−\mathrm{2}+{m}+{m}^{\mathrm{2}} =\mathrm{4}{m}−\mathrm{2} \\ $$

Commented by123456 last updated on 27/Apr/15

a(m,m)= { (m,(m≤0)),((2m^2 ),(m>0)) :}  m≤0  a(m,m)=m  m>0  a(m,m)=ma(0,m−1)+m+m^2   a(0,m−1)=m−1  a(m,m)=m(m−1)+m+m^2   =m^2 −m+m+m^2   =2m^2

$${a}\left({m},{m}\right)=\begin{cases}{{m}}&{{m}\leqslant\mathrm{0}}\\{\mathrm{2}{m}^{\mathrm{2}} }&{{m}>\mathrm{0}}\end{cases} \\ $$ $${m}\leqslant\mathrm{0} \\ $$ $${a}\left({m},{m}\right)={m} \\ $$ $${m}>\mathrm{0} \\ $$ $${a}\left({m},{m}\right)={ma}\left(\mathrm{0},{m}−\mathrm{1}\right)+{m}+{m}^{\mathrm{2}} \\ $$ $${a}\left(\mathrm{0},{m}−\mathrm{1}\right)={m}−\mathrm{1} \\ $$ $${a}\left({m},{m}\right)={m}\left({m}−\mathrm{1}\right)+{m}+{m}^{\mathrm{2}} \\ $$ $$={m}^{\mathrm{2}} −{m}+{m}+{m}^{\mathrm{2}} \\ $$ $$=\mathrm{2}{m}^{\mathrm{2}} \\ $$

Commented byprakash jain last updated on 28/Apr/15

a(5,5)=5a(0,4)+5+5^2   =5×4+5+25=50  a(10,10)=10×9+10+10^2 =200

$${a}\left(\mathrm{5},\mathrm{5}\right)=\mathrm{5}{a}\left(\mathrm{0},\mathrm{4}\right)+\mathrm{5}+\mathrm{5}^{\mathrm{2}} \\ $$ $$=\mathrm{5}×\mathrm{4}+\mathrm{5}+\mathrm{25}=\mathrm{50} \\ $$ $$\mathrm{a}\left(\mathrm{10},\mathrm{10}\right)=\mathrm{10}×\mathrm{9}+\mathrm{10}+\mathrm{10}^{\mathrm{2}} =\mathrm{200} \\ $$

Terms of Service

Privacy Policy

Contact: info@tinkutara.com